Influence of previous acid etching on interface morphology and bond strength of self-etching adhesive to cavosurface enamel - Lima, Adriano Fonseca (Dental Investigations Society, 2012)
OBJECTIVES: The aim of this study was to evaluate the (1) bond strength of a etch-and-rinse and self-etching adhesive systems to cavosurface enamel, (2) influence of the previous acid etching with phosphoric acid 35% to the self-etching adhesive application on bond strength values, and (3) analysis of the cavosurface enamel morphology submitted to different types of conditioning, with the use of a scanning electronic microscope (SEM). METHODS: Twenty four human third molars were sectioned on mesio-distal direction, resulting in two slices. The specimens were ground flat with 600-grit aluminum oxide papers, and were randomly divided into three groups: Group 1 (etch-and-rinse adhesive system (control group)), Group 2 (self-etching adhesive), and Group 3 (self-etching adhesive with previous 35% phosphoric acid-etching for 15 s). Four cylinders (0.75 mm of diameter, 1 mm height) were confectioned prior to the microshear test. Four samples for each group were prepared according the cavosurface enamel treatment and were analyzed in an SEM. RESULTS: Group 3 had the highest values on bond strength to cavosurface enamel compared to the other two groups, which presented statistically similar values. The performance of acid etching before the application of the self-etching adhesive results in an etching pattern that is different than the other groups, favoring the adhesion to the cavosurface enamel. CONCLUSIONS: Acid etching increases the bond strength values of the self-etching adhesive to cavosurface enamel, promoting a conditioning pattern that favors the adhesion to this substrate.